"Prepare all that we play!": Organizing spaces, enabling games and teaching experience in early childhood education stage - Márcia Buss Simão; Caroline Gralik; Flávia Steinbech; Eloisa Acires Candal Rocha (Universidade Federal de Santa Catarina, 2014)
This paper stems from experiences and reflections made during the supervised training in Early Childhood Education, Pedagogy course at the Federal University of Santa Catarina. That stage was held at Anjo da Guarda Daycare, owned by municipal Florianópolis, located in the Trindade neighborhood, more specifically on the hill of Morro da Penitenciária and Group 2, which was composed of 15 children of approximately one year and a half to two years old. With the goal of teaching experience, from observations, records and daily reflections on actions, relationships, interactions, games and languages of children, the focus of interventions consisted in organizing spaces to amplify the possibilities of play and group autonomy as well as enhance the time of feeding.